Asymptomatic Herpes Simplex Virus Type 1 Infection Causes an Earlier Onset and More Severe Experimental Autoimmune Encephalomyelitis - Duarte, Luisa F.; Altamirano-Lagos, María J.; Tabares-Guevara, Jorge H.; Opazo, Ma. Cecilia; Díaz, Máximo; Navarrete, Romina; Muza, Catalina; Vallejos, Omar P.; Riedel, Claudia A.; Bueno, Susan M.; Kalergis, Alexis M.; González, Pablo A. (Frontiers in Immunology, 2021)
Multiple sclerosis (MS) is an increasingly prevalent progressive autoimmune and debilitating chronic disease that involves the detrimental recognition of CNS antigens by the immune system. Although significant progress has been made in the last decades on the biology of MS and the identification of novel therapies to treat its symptoms, the etiology of this disease remains unknown. However, recent studies have suggested that viral infections may contribute to disease onset. Interestingly, a potential association between herpes simplex virus type 1 (HSV-1) infection and MS has been reported, yet a direct relationship among both has not been conclusively demonstrated. Experimental autoimmune encephalomyelitis (EAE) recapitulates several aspects of MS in humans and is widely used to study this disease. Here, we evaluated the effect of asymptomatic brain infection by HSV-1 on the onset and severity of EAE in C57BL/6 mice. We also evaluated the effect of infection with an HSV-1-mutant that is attenuated in neurovirulence and does not cause encephalitis. Importantly, we observed more severe EAE in mice previously infected either, with the wild-type (WT) or the mutant HSV-1, as compared to uninfected control mice. Also, increased EAE onset was seen after WT virus inoculation. These findings support the notion that a previous exposure to HSV-1 can accelerate and enhance EAE, which suggests a potential contribution of asymptomatic HSV-1 to the onset and severity of MS.